Green Entrepreneurship Batik Wijaya, a Strategy to Increase the Income of Pungsari Village Community, Plupuh Subdistrict, Sragen Regency - Rahmawati, Rahmawati; Amperawati, Endang Dwi; Nurlaela, Siti; Rochmatullah, Mahameru Rosy; Arifah, Siti (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2024)
This community service activity was carried out in the Pungsari area, Plupuh District, Sragen Regency, in collaboration with UKM Batik Wijaya and the Sragen Regency Government. The purpose of this activity is to foster green entrepreneurship at a UKM Batik Wijaya so that it can increase the income of the surrounding community while still paying attention to the concept of environmentally sound business sustainability. UKM Batik Wijaya produces batik products that are not inferior when compared to other SMEs. Participation of participants in this activity shows high enthusiasm in an effort to increase creativity and innovation in the production of UKM Wijaya. After the implementation of this activity, it is hoped that it can increase the income of the community, especially those who are members of UKM Wijaya and create a healthier environment in Pungsari Village.